Glutaminase 2 knockdown reduces hyperammonemia and associated lethality of urea cycle disorder mouse model. Issue 3 (4th February 2022) - Mao, Xia; Chen, Helen; Lin, Allen Z.; Kim, Sun; Burczynski, Michael E.; Na, Erqian; Halasz, Gabor; Sleeman, Mark W.; Murphy, Andrew J.; Okamoto, Haruka; Cheng, Xiping
Abstract: Amino acids, the building blocks of proteins in the cells and tissues, are of fundamental importance for cell survival, maintenance, and proliferation. The liver plays a critical role in amino acid metabolism and detoxication of byproducts such as ammonia. Urea cycle disorders with hyperammonemia remain difficult to treat and eventually necessitate liver transplantation. In this study, ornithine transcarbamylase deficient ( Otc spf‐ash ) mouse model was used to test whether knockdown of a key glutamine metabolism enzyme glutaminase 2 (GLS2, gene name: Gls2 ) or glutamate dehydrogenase 1 (GLUD1, gene name: Glud1 ) could rescue the hyperammonemia and associated lethality induced by a high protein diet. We found that reduced hepatic expression of Gls2 but not Glud1 by AAV8‐mediated delivery of a short hairpin RNA in Otc spf‐ash mice diminished hyperammonemia and reduced lethality. Knockdown of Gls2 but not Glud1 in Otc spf‐ash mice exhibited reduced body weight loss and increased plasma glutamine concentration. These data suggest that Gls2 hepatic knockdown could potentially help alleviate risk for hyperammonemia and other clinical manifestations of patients suffering from defects in the urea cycle. Abstract :